JUDICATURE IN THE CENTRAL CAUCASUS IN THE END OF THE 1850S IN THE CONTEXT OF RUSSIAN JUSTICE SYSTEM - Elena Kobakhidze; Anzhela Dzottsoeva (Гуманитарные и юридические исследования)
The article analyses judicature in the Central Caucasus as formed by the end of the 1850s on the basis of legal acts of the previous decades. The article shows that the regional justice system evolved by analogy with the Russian one, but had its own features that were determined by the peculiarities of regional administering. The principles of administering and legal proceedings differed according to the category of population. Russian justice system adapted to the conditions of the Caucasus vicegerency was valid for civilians, while for tmountain dwellers specific mechanisms of judicature and legal proceedings were gradually developed. In accordance with them, the state law was brought into correlation with local juridical practice.